Resilience to extreme flooding shown by both hydric and mesic wetland plant species. Issue 8 (24th October 2019) - Brotherton, Sarah J.; Joyce, Chris B.; Berg, Maureen J.; Awcock, Graeme J.
Abstract: Global climate change models forecast an increasing frequency and duration of extreme flood events, including during the growing season. In this mesocosm experiment, the survival, growth, and flowering of two hydric and two mesic wetland plant species were monitored under two extreme flood regimes, namely, repeated 2‐ and 7‐day floods, and compared with unflooded conditions. Plant survival was not significantly affected by flooding, but species showed different growth and flowering responses to the flood regimes. The hydric species Cardamine pratensis showed contrasting responses to floods with significantly more flowering stems and longer leaves in the 2‐day regime but delayed and poorer flowering in the 7‐day regime. Juncus articulatus, the other hydric species, responded most actively to 7‐day flooding, with significantly longer leaves, taller and more abundant flowering stems, and more flowers than in unflooded conditions. The mesic species Ranunculus acris showed variable growth and phenological responses to flooding, whereas Scorzoneroides autumnalis was most affected by the 7‐day flood regime, producing significantly shorter leaves and flowering stems and fewer flowers earlier in the season, compared with unflooded conditions. Overall, repeated 7‐day floods had a greater impact on plant performance than 2‐day flood events. All four species showed resilience to extreme flooding, irrespective of whether they were classed as hydric or mesic, but there was differential tolerance between species. This suggests that wetlands should be able to sustain vegetation under flooding extremes induced by climate change but community composition, biodiversity, and wetland services will all be affected.